Missed opportunity of deworming a Maasai boy from nomadic family leading to life threatening intestinal obstruction. Issue 5 (26th May 2020) - Pyuza, Jeremia J; Andongolile, Alice A; Issangya, Christain E; Msuya, David; Yahaya, James J; Shao, Elichilia R; Mremi, Alex R
Abstract: : Mass deworming against soil-transmitted helminthiasis, including Ascaris lumbricoides (AL), is one of the largest public health interventions in low- and middle-income countries. The prevalence of A. lumbricoides in Tanzania is 6.8%. We present a 3-year-old male of a known Tanzanian nomadic tribe (Masaai tribe) with history of missed deworming, who was brought to the emergency department with a 3-day history of constipation, nonprojectile, bilious vomiting, generalized abdominal distension and pain. : He was diagnosed with intestinal obstruction by the use of a plain abdominal X-ray, which revealed marked gaseous distension of the stomach and bowels without significant air-fluid levels. He was initially treated with intravenous ceftriaxone 50 mg/kg, metronidazole 15 mg/kg and acetaminophen 15 mg/kg. An explorative laparotomy was then performed. Intraoperative findings demonstrated a dense collection of A. lumbricoides worms in the gangrenous proximal jejunum and duodenum. Thorough abdominal lavage was carried out and abdomen was closed.